2022
DOI: 10.1007/s00382-022-06289-y
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the large-scale drivers of precipitation in the northeastern United States via linear orthogonal decomposition

Abstract: This study examines the linear orthogonal modes associated with monthly precipitation in the northeastern United States, from CESM1 LENS (35 ensemble members, 1979–2005) and two reanalysis datasets (ERA5, 1950–2018 and NOAA-CIRES-DOE 20CRv3, 1950–2015). Calendar months are aggregated together, and any linear trends in data are removed. Using region-averaged precipitation anomaly time series and monthly anomalies for several global 2D atmospheric fields, a linear orthogonal decomposition method is implemented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…11i) than is observed in cluster 1. Given the importance of southerly IVT along the Atlantic seaboard for providing moisture to this region (Sukhdeo et al 2022), these results provide additional context for the Q850 anomalies discussed below. As the midlevel streamfunction LSMPs develop, they act to divert the normal IVT away from the Northeast, leading to negative Q850 anomalies there during the onset period.…”
Section: Thermodynamical Differences Driving Two Types Of Dry Spellsmentioning
confidence: 74%
See 1 more Smart Citation
“…11i) than is observed in cluster 1. Given the importance of southerly IVT along the Atlantic seaboard for providing moisture to this region (Sukhdeo et al 2022), these results provide additional context for the Q850 anomalies discussed below. As the midlevel streamfunction LSMPs develop, they act to divert the normal IVT away from the Northeast, leading to negative Q850 anomalies there during the onset period.…”
Section: Thermodynamical Differences Driving Two Types Of Dry Spellsmentioning
confidence: 74%
“…Extratropical cyclones (ETCs) and their tracks play a key role in the seasonal cycle of precipitation in the Northeast (Kunkel et al 2012;Pfahl and Wernli 2012;Agel et al 2015;Sukhdeo et al 2022). There are generally two broad regions with the highest storm track densities: one over the Great Lakes region and another along the Atlantic seaboard (Hoskins and Hodges 2002;Kocin and Uccellini 2004;Pfahl and Wernli 2012;Agel et al 2015).…”
Section: Changes In Etc Activity and Storm-track Density During Dry S...mentioning
confidence: 99%
“…Additionally, given the modest PV200 anomalies for the unclassified EPE with a lower precipitation rate, we see chances to incorporate quantitative analysis between atmospheric drivers and precipitation rates. Some quantitative analysis, like Sukhdeo et al (2022), could be used to quantify the predictability. Overall, the work presented here aims to better quantify the relative importance of meteorological drivers to EPEs in different monsoonal subregions.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Sukhdeo et al. (2022) applied linear orthogonal decomposition to identify the large‐scale atmospheric drivers of precipitation over the NEUS. While they did tie ETC activity into their analysis, the focus is primarily on the dynamics behind monthly precipitation variability.…”
Section: Introductionmentioning
confidence: 99%
“…They found that extreme precipitation days were typically accompanied by a collocated deep upper-level trough and pronounced ridge downstream. Similarly, Sukhdeo et al (2022) applied linear orthogonal decomposition to identify the large-scale atmospheric drivers of precipitation over the NEUS. While they did tie ETC activity into their analysis, the focus is primarily on the dynamics behind monthly precipitation variability.…”
mentioning
confidence: 99%